2015
DOI: 10.4103/2008-7802.166503
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the Nottingham Prognosis Index and the adjuvant online decision making tool for prognosis in early-stage breast cancer patients

Abstract: Background:Prognostic tools are widely used in the practice of Oncology and have been developed to help stratify patients into specific risk-related grouping. We sought to apply of two such tools used for patients with early-stage breast cancer and to correlate them with actual outcomes.Methods:A retrospective study was designed to include early-stage breast cancer cases seen from 1994 to 2014 at the Seyedoshohada Hospital in Isfahan, Iran. Information was derived from the patients’ records, and indices were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Jung et al (2013) [44]LowModerateModerateLow22Kindts et al (2016) [135]ModerateModerateModerateLow23Kollias et al (1999) [31]ModerateModerateLowModerate24Kuo et al (2012) [62]LowLowModerateLow25Laas et al (2015) [68]ModerateModerateModerateLow26Lende et al (2010) [136]LowModerateLowLow27M. Liu et al (2010) [74]LowModerateLowLow28Maishman et al (2015) [137]ModerateModerateLowLow29Megha et al (2010) [70]ModerateModerateLowLow30Miao et al (2016) [138]ModerateHighLowLow31Michaelson et al (2011) [42]LowHighLowModerate32Mojir Sheibani et al (2013) [65]LowLowModerateLow33Mook et al (2009) [64]LowModerateModerateLow34Okugawa et al (2009) [52]LowLowLowLow35Olivotto et al (2005) [45]LowHighLowLow36Plakhins et al (2013) [63]ModerateModerateLowLow37Quintyne et al (2013) [60]LowModerateModerateLow38Rejali et al (2015) [54]Moderate…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al (2013) [44]LowModerateModerateLow22Kindts et al (2016) [135]ModerateModerateModerateLow23Kollias et al (1999) [31]ModerateModerateLowModerate24Kuo et al (2012) [62]LowLowModerateLow25Laas et al (2015) [68]ModerateModerateModerateLow26Lende et al (2010) [136]LowModerateLowLow27M. Liu et al (2010) [74]LowModerateLowLow28Maishman et al (2015) [137]ModerateModerateLowLow29Megha et al (2010) [70]ModerateModerateLowLow30Miao et al (2016) [138]ModerateHighLowLow31Michaelson et al (2011) [42]LowHighLowModerate32Mojir Sheibani et al (2013) [65]LowLowModerateLow33Mook et al (2009) [64]LowModerateModerateLow34Okugawa et al (2009) [52]LowLowLowLow35Olivotto et al (2005) [45]LowHighLowLow36Plakhins et al (2013) [63]ModerateModerateLowLow37Quintyne et al (2013) [60]LowModerateModerateLow38Rejali et al (2015) [54]Moderate…”
Section: Resultsmentioning
confidence: 99%
“…At the outset, a patient will be classified into one of three prognostic groups based on their NPI score: good prognostic group (PI< 3.4), moderate prognostic group (3.4 ≤ PI≤5.4), and poor prognostic group (PI> 5.4) [ 53 ]. Some validation studies of the NPI further divided the samples into six smaller prognostic groups [ 47 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average times to censor were 9.2 (4.8 SDs) and 9.5 (4.9) years, for each set, respectively. The resulting Bayesian model and data from METABRIC were used to integrate COVs (including age at the moment of diagnosis (AGE), CS, type of carcinoma (TC), the NPI, 32 and treatment), whole-genome GE profiles, copy number variants (CNVs), and interactions between these omics and treatments. The NPI consists of a well-validated prognostic score that takes information from tumor size, grade, and nodal involvement, specifically NPI= (0.417 × size)+(0.76 × lymph-node stage)+(0–82 × tumor grade), typically ranging between 2 and 7; 33 the higher the score the shorter the lifespan prognosis for the patient.…”
Section: Methodsmentioning
confidence: 99%
“…The earliest data reported in the published studies came from 1970 [ 42 ] and most recent data from 2014 [ 43 ] (see Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 2 ] compared two datasets: from Finland and the USA. Single studies reported data from each of Canada [ 42 ], Japan [ 35 ], South Korea [ 32 ], Hong Kong [ 27 ] and Iran [ 43 ]. Study reporting quality was generally assessed as satisfactory, and risk of bias in relation to the study survival estimates was considered to be low for all included studies (see Additional file 1 : Appendix 3).…”
Section: Resultsmentioning
confidence: 99%